Does galactomannan testing increase diagnostic accuracy for IPA in the ICU? A prospective observational study. Issue 1 (December 2016) - Schroeder, Maria; Simon, Marcel; Katchanov, Juri; Wijaya, Charles; Rohde, Holger; Christner, Martin; Laqmani, Azien; Wichmann, Dominic; Fuhrmann, Valentin; Kluge, Stefan
Abstract Background An algorithm for distinguishing invasive pulmonary aspergillosis (IPA) in critically ill patients (AspICU) has been proposed but not tested. Methods This was a prospective observational study applying the AspICU protocol to patients with positive Aspergillus culture (PAC group) and those with negative aspergillus culture but positive galactomannan test in respiratory tract samples (only positive galactomannan (OPG group)). Patients underwent a standardized diagnostic workup with bronchoscopy, computed tomography (CT), and galactomannan determination in serum and bronchoalveolar lavage fluid (BALF). Results We included 85 patients in the study. Of these, 43 had positive aspergillus cultures and 42 patients had only a positive galactomannan test. There were no statistically significant differences in baseline characteristics, underlying conditions or ICU scores between the two groups. The galactomannan titre in BALF was significantly higher in the positive aspergillus culture (PAC) group (enzyme immunoassay (EIA) 5.9, IQR 3.2–5.7) than in the OPG group (EIA 1.7, IQR 0.9–4.5) (p < 0.001). Classic features of IPA were detected on CT in 37.5 % and 36.6 % of patients in the PAC and OPG groups, respectively. There were no statistically significant differences between the PAC and the OPG group in relation to AspICU or European Organization for the Research and Treatment of Cancer (EORTC) criteria. A positive aspergillus culture was a stronger trigger for initiating antimycotic treatment than positive BALF galactomannan: 88.4 % of patients in the PAC group were regarded by clinicians as having IPA and received antimycotic treatment as opposed to 59.5 % in the OPG group (p = 0.002). The 180-day mortality was 58.1 % in the PAC group and 59.5 % in the OPG group. Conclusions The inclusion of BALF galactomannan as an additional entry criterion for the AspICU clinical algorithm could increase the diagnostic sensitivity for IPA in ICU patients. Trial registration The study was registered at ClinicalTrials.gov (registration numberNCT01866020 ) on 27 May 2013.